Hadith-Based Moral Education: Buya Mawardi Muhammad’s Legacy at Perguruan Thawalib Padang Panjang - Firman Firman; Widia Fithri; Riri Fitria (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Buya Mawardi Muhammad is a distinguished Islamic scholar, recognised as a senior educator at the Thawalib Padang Panjang Islamic Boarding School and for his extensive scholarly publications. His distinctive contribution lies in the compilation of hadith books expressly intended to enhance the moral education of students—an approach rarely found in the pesantren literary tradition. The ethical principles included in these hadith books remain relevant, transmitted for generations, and are still imparted at Perguruan Thawalib (Thawalib School), Padang Panjang. This study aims to examine the contributions of Buya Mawardi Muhammad to the development of moral education through his hadith works and their impact on students' character formation, particularly at Thawalib Padang Panjang. This study employs a qualitative approach that is based on a literature review. Primary data were taken from three hadith books by Buya Mawardi: Jawāhir al-Aḥādīth al-Nabawiyyah, al-Aḥādīth al-Mukhtārah, and al-Aḥādīth al-Mukhtārah wa Syarḥuhā, while secondary data were gathered through interviews with his descendants, students who had studied with him, and leading figures from the Thawalib. Using content analysis facilitated by ATLAS.ti software, several key findings emerged. First, Buya Mawardi's works significantly contribute by systematically compiling hadith literature focused on three main themes: ethics or character (akhlak), creed (aqidah), and worship (ibadah). These books are systematically organised and designed for various educational levels, ranging from three years of tsanawiyah (junior high school) to three years of 'aliyah (senior high school, or Kulliyatul Ulūm al-Islāmiyyah). Second, the impact of Buya Mawardi's teachings can be seen in the formation of students' character, marked by virtuous conduct, scholarly enthusiasm, and a commitment to social values such as empathy, solidarity, and generosity. This study helps improve hadith studies related to moral education in pesantren (Islamic boarding schools) in Minangkabau and enhances the understanding of Islamic teaching methods that are relevant to today's social and cultural issues in Indonesia.